Wintering ecology of sympatric subspecies of Sandhill Crane: Correlations between body size, site fidelity, and movement patterns. (9th September 2015) - Ivey, Gary L.; Dugger, Bruce D.; Herziger, Caroline P.; Casazza, Michael L.; Fleskes, Joseph P.
Abstract: Body size is known to correlate with many aspects of life history in birds, and this knowledge can be used to manage and conserve bird species. However, few studies have compared the wintering ecology of sympatric subspecies that vary significantly in body size. We used radiotelemetry to examine the relationship between body size and site fidelity, movements, and home range in 2 subspecies of Sandhill Crane ( Grus canadensis ) wintering in the Sacramento–San Joaquin Delta of California, USA. Both subspecies showed high interannual return rates to the Delta study area, but Greater Sandhill Cranes ( G. c. tabida ) showed stronger within-winter fidelity to landscapes in our study region and to roost complexes within landscapes than did Lesser Sandhill Cranes ( G. c. canadensis ). Foraging flights from roost sites were shorter for G. c. tabida than for G. c. canadensis (1.9 ± 0.01 km vs. 4.5 ± 0.01 km, respectively) and, consequently, the mean size of 95% fixed-kernel winter home ranges was an order of magnitude smaller for G. c. tabida than for G. c. canadensis (1.9 ± 0.4 km 2 vs. 21.9 ± 1.9 km 2, respectively). Strong site fidelity indicates that conservation planning to manage for adequate food resources around traditional roost sites can be effective for meeting the habitat needs of these cranes, but the scale of conservation efforts should differ by subspecies. Analysis of movement patterns suggests that conservation planners and managers should consider all habitats within 5 km of a known G. c. tabida roost and within 10 km of a G. c. canadensis roost when planning for habitat management, mitigation, acquisition, and easements.